Formulation and evaluation of atenolol floating bioadhesive system using optimized polymer blends - Siddam, Haritha; G. Kotla, Niranjan; Maddiboyina, Balaji; Singh, Sima; Sunnapu, Omprakash; Kumar, Anil; Sharma, Dinesh (International Journal of Pharmaceutical Investigation)
Introduction: Oral sustained release gastro retentive dosage forms offer several advantages for drugs having absorption from the upper gastrointestinal tract to improve the bioavailability of medications which have narrow absorption window. The aim of the study was to develop a floating bioadhesive drug delivery system exhibiting a unique combination of floatation and bioadhesion to prolong the residence in the stomach using atenolol as a model drug. Methods: Prior to compression, polymeric blend(s) were evaluated for flow properties. The tablets were prepared by direct compression method using bioadhesive polymer like Carbopol 934P and hydrophilic polymers like HPMC K4M, HPMC K15M, and HPMC K100M. The prepared tablets were evaluated for physical characteristics, bioadhesive strength, buoyancy lag time, swelling index and in vitro drug release studies. Results: The mean bioadhesive strength was found to be in the range of 16.2 to 52.1 gm. The optimized blend (F11) showed 92.3% drug releases after 24 hrs. Whilst, increase in concentration of carbopol 934P, bioadhesive strength and swelling index was increased with slow release. The n values of optimized formulations were found in the range of 0.631-0.719 indicating non-fickian anomalous type transport mechanism. Conclusion: The study aided in developing an ideal once-a-day gastro retentive floating drug delivery system with improved floating, swelling and bioadhesive characteristics with better bioavailability.
Keywords: Atenolol; Carbopol 934P; gastro retentive floating bioadhesive tablets; HPMC K4M; HPMC K15M; HPMC K100M; polymer blends